2012
DOI: 10.1620/tjem.227.161
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin Attenuates Post-Infarct Myocardial Remodeling by Down-Regulating the NF-κB Pathway

Abstract: Myocardial infarction (MI) leads to progressive left ventricular (LV) dilatation and is associated with interstitial fibrosis in the non-infarcted myocardium. The NF-κB signaling pathway plays an important role in ventricular remodeling after MI. Recent studies have indicated that the anti-malarial agent artemisinin can inhibit NF-κB activation, which may attenuate post-infarct myocardial remodeling. In this study, we investigated the effect of artemisinin on post-infarct myocardial remodeling using a rat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Indeed, half of the 2015 Nobel Prize in Physiology and Medicine was awarded to the investigator who discovered artemisinin, a drug that is estimated to reduce malaria-associated mortality by 20% overall, and by >30% in children [28]. Artemisinin was previously shown to reduce LV hypertrophy in rat models of pressure overload and myocardial infarction, in association with blunted NF-κB signaling in the heart [29,30]. Unlike artemisinin, which is a natural product, artesunate is a semisynthetic derivative that has improved solubility, bioavailability and anti-malarial activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, half of the 2015 Nobel Prize in Physiology and Medicine was awarded to the investigator who discovered artemisinin, a drug that is estimated to reduce malaria-associated mortality by 20% overall, and by >30% in children [28]. Artemisinin was previously shown to reduce LV hypertrophy in rat models of pressure overload and myocardial infarction, in association with blunted NF-κB signaling in the heart [29,30]. Unlike artemisinin, which is a natural product, artesunate is a semisynthetic derivative that has improved solubility, bioavailability and anti-malarial activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that NF-jB signaling pathway play a vital role in the development of this process. Previous studies have shown that the stimulation or induction of MMPs at the transcriptional level is regulated by a variety of growth factors and inflammatory cytokines, many of them are modulated by NF-jB [25]. NF-jB, a heterodimeric cytosolic protein, is kept inactive in resting cells by binding with a member of the IKBa inhibitor protein family.…”
Section: Discussionmentioning
confidence: 99%
“…The LV was cut into 5 mm sections and stained with Masson's trichrome. Images were acquired at 400x magnification using a fluorescence microscopy, and the degree of interstitial fibrosis and perivascular fibrosis were determined using Image-Pro Plus 6.0 software (Media Cybernetics, Rockville, MD, USA) as previously described [48] .…”
Section: Methodsmentioning
confidence: 99%